Option-Style Multi-Factor Comparable Company Valuation for Practical Use - Matthias Meitner (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
Classical single-factor comparable company valuation (CCV) like e.g. valuation using the price-earnings ratio is associated with several shortcomings. The two most important are the non-applicability of negative values in the basis of reference and the high requirements to the qualitative characteristics of comparable companies. This paper develops a multi-factor CCV model based on substance and performance related accounting attributes that largely overcomes these drawbacks. Additionally, the model allows to depict expected future earnings development economically sounder than single-factor models. Furthermore, by accounting for management?s option to adapt firm assets differently or to liquidate the company the model can conclusively assign positive stock prices to currently negatively performing companies.
Keywords: M41; G12; M21; G31; 330; Valuation; Multiples; Real Options; Unternehmensbewertung; Wirtschaftsmodell; Realoption; Theorie